Perkembangan kondisi pasien sindrom nefrotik anak setelah pemberian asuhan gizi di Rumah Sakit Umum Dr. Moch. Shaleh Probolinggo - Diningrum, Razita Lauzah; Adi, Dhuha Itsnanisa; Nurika, Globila; Indrayani, Reny; Syamila, Ana Islamiyah (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Nefrotik syndrome (NS) is the most common kidney disorder found in children with an incidence rate of up to 15 times more than in adults. Clinical conditions due to disease progression and the effects of NS treatment require adjustments in terms of diet, so it requires a proper diet to suppress disease progression and improve the quality of life of patients.Objectives: The aim of this study is to determine the effect of nutritional care on the development of the condition of pediatric NS patients.Methods: This study is a case report of nutritional care of NS patients for 3 days. The study was conducted at Dr. Mohamad Saleh Probolinggo Regional Public Hospital. The subjects in this study was adolescents aged 17 years and 10 months with NS. The data obtained are tabulated and analyzed descriptively.Results: After providing nutritional care for 3 days, it was seen that the nutritional status of patients before and after the intervention was classified as good nutritional status, the patient's albumin levels increased from 2,2 mg/dL to 3,3 mg/dL. The patient's physical condition showed a reduction in edema in the feet and hands. The average energy intake has met the adequacy of intake which is 82,5%, 85,7% and 92,57 %.Conclusion: Nutritional care produces a positive influence on NS patients at Dr. Moch Shaleh Probolinggo Regional Public Hospital. Providing education to patients and patients' families by nutritionists needs to be done regularly so that patients have the motivation to run a given diet properly.Keywords Nefrotik Syndrome, nutritional status, nutritional care, disease progression